Risk factors associated with Bovine Viral Diarrohea seroprevalence in non-vaccinated cows and heifer in the Bolívar Municipality of Yaracuy state, Venezuela (Gaceta de Ciencias Veterinarias, 2017)
Bovine Viral Diarrohea (BVD) is an infectious bovine disease caused by a Pestivirus. It causes significant economic losses in the livestock industry and is characterized by abortion, stillbirths, birth of weak offspring, neurological problems and congenital malformations. In order to determine the risk factors associated with the seroprevalence of this disease in non-vaccinated cows and heifers in the Bolivar Municipality of Yaracuy State, a seroepidemiological sampling was carried out on 460 animals from 42 farms. The presence of antibodies to the virus was determined using the indirect ELISA technique and its association with risk factors such as age group, herd size and animal origin was determined by a multivariate binary logistic regression with a 95% confidence interval, the significance was estimated by determining the odds ratio (OR) of each factor with a value of p < 0.05. Calculations were performed using the statistical package SPSS® version 15.0. The prevalence of BVD found was 55.43% and its associated risk factors were age group cow (OR = 1.76) and herd size (OR = 1.55). It was possible to identify the presence of antibodies to the BVD virus in a high percentage of females in unvaccinated herds, showing that the number of positive animals increased with age and that the size of the herd influenced the diffusion of the virus, while that the origin of the animal was not associated with the seropositivity of the disease studied.
Keywords: Seroprevalence, BVD, risk factors; Seroprevalence; BVD; risk factors